1975
DOI: 10.1051/jphyslet:01975003605011300
|View full text |Cite
|
Sign up to set email alerts
|

How does the elastic scattering of 12C + 20Ne compare with that of 16O + 16O ?

Abstract: Résumé. -

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1976
1976
1980
1980

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The results are shown in figure 2 together with the results of Doubre et al [3]. It is seen that the observed cross-sections at 90~ and beyond are of the order of the two estimates of the compound nuclear crosssections.…”
Section: 375mentioning
confidence: 65%
See 2 more Smart Citations
“…The results are shown in figure 2 together with the results of Doubre et al [3]. It is seen that the observed cross-sections at 90~ and beyond are of the order of the two estimates of the compound nuclear crosssections.…”
Section: 375mentioning
confidence: 65%
“…In a recent communication [3] of another study of 12C + 2°Ne elastic scattering were reported. In this work the excitation functions at more backward angles, 90° and 1300, were measured as well as at 700 c.m.…”
Section: 375mentioning
confidence: 97%
See 1 more Smart Citation